Identifying Predictors of Parents' and Children's Participation and Barriers in Randomized Clinical Trials. (29th May 2020) - Clayton, Priscilla; Palacios,, Cristina
Abstract: Objectives: Background: Randomized controlled trials are considered the 'gold standard' to assess the efficacy and effectiveness of health care and dietary interventions, however, challenges with recruitment and retention of participants can be detrimental to the validity and generalizability of the study. Children and adolescents play a role in the decision to participate, although parents are the primary decision-makers. Exploring children and parent's knowledge, attitudes, and perceptions towards research can help to understand factors that influence participation and retention. Objective: To identify predictors of recruitment and retention in RCTs involving both parents and children to assist in the implementation of recruitment and retention strategies. Methods: A systematic review of RCTs was conducted to explore the available evidence to compose a qualitative meta-summary. Studies were identified from 3 databases and restricted only to English language publications. Data reporting participant's predictors and barriers of recruitment and retention in RCTs involving children and adolescents aged 0 to 21 were identified. Year of publication ranged from 2006 to 2019. Studies not including children and studies not involving participant feedback were excluded. Results: 53 records were identified; 32 were excluded due to exclusion of child and/or parent feedback, therefore 21 studies were included. Several themes were identified between parents and children that mentioned predictors: personal health benefit, altruism, trust in the research, contact with staff, benefit for parents themselves, benefit for the community, minimal risk to the child, monetary benefits, felt as the only option, influence by family and friends, recommendation from physician, and increase in knowledge. Barriers mentioned were: felt as the "guinea pig, " burden for child, decision too stressful, fear of randomization, no direct benefit, and time and financial constraints. The most common themes identified in several of the studies were personal health benefits, the risk to the child, altruism, time constraint, and no direct benefit. Conclusions: Important predictors of recruitment and retention in RCTs are children's personal health benefits and risks, altruism, time constraint, and no direct benefit. Funding Sources: NIH